Subepithelial Serotonin Reduces Small Intestinal Epithelial Cell Tightness via Reduction of Occluding Expression - Horie, Hideki; Handa, Osamu; Naito, Yuji; Majima, Atsushi; Yasuda-Onozawa, Yuriko; Uehara, Yukiko; Kamada, Kazuhiro; Katada, Kazuhiro; Uchiyama, Kazuhiko; Ishikawa, Takeshi; et al. (Turkish Journal of Gastroenterology, 2022)
Background: The precise pathogenesis of irritable bowel syndrome (IBS) remains unresolved; however, recent studies have reported that patients with diarrhea-predominant IBS exhibit an increased small intestinal permeability and increased number of enterochromaffin cells containing high 5-hydroxytryptamine (5HT; serotonin) levels. In this study, we investigated whether 5HT has the potential to modulate small intestinal epithelial cell permeability, focusing on tight junction-associated proteins. Methods: The differentiated Caco-2 cell monolayer on porous filters (Millicell) was used. Then, 5HT was added to the lower Millicell compartment for 7 days. Intestinal epithelial cell permeability was assessed by measuring the flux of paracellular permeability markers. We further assessed the expression of occludin in the 5HT-stimulated Caco-2 monolayer. Results: We found that 5HT did not affect the viability of Caco-2 cells at concentrations up to 100 µM during the experimental period. Administration of 5HT to the basal side of Caco-2 cells increased the flux of 3H-labeled mannitol (182 Da) but did not increase that of FITC-dextran (4000 Da). Among the tight junction proteins, the expression of occludin was specifically decreased by stimulation with 5HT at a concentration of 100 µM. Conclusion: In conclusion, excessive 5HT in the basal side increased the permeability of intestinal epithelial cells via reduction of occludin expression.